Association of I/D angiotensin-converting enzyme genotype with erythropoietin stimulation in kidney failure - Savin Marina; Hadzibulic Edvin; Damnjanović Tatjana; Santric Veljko; Stankovic Sanja (Archives of Biological Sciences, 2017)
Angiotensin-converting enzyme (ACE)-gene polymorphism is a possible predisposing factor of erythropoietin response under hypoxic conditions. However, it is not completely clear whether the ACE insertion/deletion (I/D) genotype has an impact on anemia in patients with permanent kidney failure. A 9-month prospective trial was conducted on 53 patients on hemodialysis aimed at determining the beneficial effect of oral vs intravenous iron in anemia management with recombinant human erythropoietin (rHuEpo), and identifying a possible association of the ACE gene I/D polymorphism with the response to rHuEpo. Patients were randomly allocated to receive 50-100 mg daily of ferrous gluconate orally (N=26) or intravenously every two weeks (N=27), together with rHuEpo-beta (200 IU/kg) subcutaneously, to achieve a hemoglobin increase to 105 g/L; subsequently the rHuEpo dose was adjusted at one or two week intervals. In 34 patients who regularly received ACE-inhibitor (ACEi) medication, genotyping for ACE-gene I/D polymorphism was performed using PCR, gel analysis and appropriate restriction digestion. After prolonged rHuEpo treatment, 24.5% of patients attained the targeted 9th-month hemoglobin concentration (105 g/L). Of these, 6/26 of patients received elemental iron orally and 7/27 received it intravenously. We observed an association between homozygous DD (deletion) of the ACE gene and a remarkable early increase in blood hemoglobin (p=0.028), erythrocyte count (p=0.020) and hematocrit (p=0.043) after reduction of the dose of rHuEpo (F=3.95; p=0.029), irrespective of the iron repletion mode (p=0.960). This is the first report on DD genotype as a linkage marker for the optimization of rHuEpo dose for anemia management in hemodialysis patients.